Isolation, Culture and Differentiation of Buffaloes Bone Marrow Mesenchymal Stem Cells Obtained from the Coxal Tuberosity - Oba, Eunice [UNESP]; Listoni, Amanda Jeronimo [UNESP]; Maia, Leandro [UNESP]; Moraes, Carolina Nogueira de [UNESP]; Landim-Alvarenga, Fernanda da Cruz [UNESP] (Int Buffalo Information Ctr, 2013)
Currently, much attention has been devoted to the renewal of knowledge about Stem Cells and Cell Therapy in domestic species. In this sense, the present work aimed to develop a methodology for collecting, processing and cultivation of mesenchymal stem cells obtained from bone marrow of coxal tuberosity in buffaloes. The collection was performed using a Komiyashiki needle, which was introduced in the coxal tuberosity and the bone marrow aspirated into a heparinized syringe with the aid of negative pressure. Directly after collection samples were processed at the laboratory at FMVZ - UNESP. The samples took approximately 32 days to reach 80% confluence, when the first passage and differentiation was performed. To confirm the mesenchymal origin, cells were induced to differentiate into adipogenic and osteogenic lineages. Samples showed morphological changes during differentiation protocol, but not all presented production of extracellular deposits of calcium or intracellular fat droplets, observed after staining with Alizarin Red and Oil Red respectively. Compared with the material obtained from other species and processed in the same laboratory, the primary culture was longer. Therefore, more studies are needed to standardize the age of animals used and to test other inducers of cell differentiation.
Keywords: bone marrow; buffalo; coxal tuberosity; cell differentiation stem cells